Enhancing Police Operations: The Impact of CCTV in Monitoring, Incident Response, and Crime Investigation in Nairobi City County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2024)
This study assessed the impact of Close Circuit Television (CCTV) on police operations in Nairobi, Kenya, focusing on its role in public space monitoring, incident response, and crime investigation. Employing a convergent parallel design informed by the Task-Technology Fit Theory, it collected data from 403 purposefully and cluster-sampled police officers through questionnaires, key informant interviews, and focus group discussions. Quantitative data analysis utilised descriptive statistics, while thematic analysis helped to uncover qualitative insights. CCTV was found to be valuable for incident awareness, traffic management, and crime detection and significantly aided in incident response and investigations. However, limited camera coverage and technical issues reduced effectiveness. The study concluded that Nairobi’s CCTV system is a valuable tool, but improvements like expanding coverage and providing storage solutions for investigators are recommended.